2002
DOI: 10.1136/bmj.325.7363.524
|View full text |Cite
|
Sign up to set email alerts
|

Health promotion for adolescents in primary care: randomised controlled trial

Abstract: Objectives To evaluate the effectiveness of inviting teenagers to general practice consultations to discuss health behaviour concerns and appropriate follow up care. Design Randomised controlled trial, with participants randomised to a consultation (intervention) or usual care (control). Questionnaires completed at baseline, 3 months, and 12 months. Setting Eight general practices in Hertfordshire, England. Participants 1516 teenagers aged 14-15 years. Intervention Consultations with practice nurses to discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
112
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(120 citation statements)
references
References 10 publications
5
112
0
3
Order By: Relevance
“…Furthermore, 80% of adolescents reported that they visit a doctor at least once in every six months (Table 2). This is consistent with research findings in other developed countries, which indicate that 70-90% of adolescents contact primary health services at least once a year [2,31]. Therefore, present practice provides opportunities for consultations with adolescents, which, if appropriately oriented, can address critical problems of this stage of development.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Furthermore, 80% of adolescents reported that they visit a doctor at least once in every six months (Table 2). This is consistent with research findings in other developed countries, which indicate that 70-90% of adolescents contact primary health services at least once a year [2,31]. Therefore, present practice provides opportunities for consultations with adolescents, which, if appropriately oriented, can address critical problems of this stage of development.…”
Section: Discussionsupporting
confidence: 78%
“…It has been shown that health professionals have credibility among adolescents and the advice they give may have a positive impact on health behavior [31]. Furthermore, studies have reported that a familiar trusted person can improve communication and adolescents are more willing to discuss topics that have been previously discussed [31]. Time available for consultation is an important parameter of increased quality in health care of adolescents, as has been consistently shown [23,24,27,32,33].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…[6][7][8] One of these studies 6 , in which young people were invited to attend a nurse-led general-practice visit reported only minor changes in participants' health-risk behaviours. The other studies, which focused on reductions in sexual-risk behaviours, reported a positive effect of the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Lule et al (2006) suggest that efforts to improve the health of young people may be even more complex and challenging than for other age groups because many of their health issues are behaviourbased and actual symptoms of CVD may not be evident, or seen as serious yet. Walker et al (2002) found few published reports of screening and health promotion in family practice settings and Walker and Townsend (1998) reported that according to 200 health care providers in 200 U. S. cities, youth are at a point when health intervention could make a difference, but that preventive, primary reproductive, and behavioural health care is not well matched to adolescent needs and preferences. The Canadian Task Force on Preventive Health care (2000) suggested that an adolescent friendly atmosphere is needed and teens reported that issues of confidentiality and access to telephone and good written information is needed.…”
Section: Treatment and Clinical Interventionsmentioning
confidence: 99%